GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

MnO2/CoFe2O4/PTFE multifunctional catalyst for PM2.5 filtration and visible-light-driven thermocatalytic degradation of toluene - Jupei Zhang; Qiancheng Zhou; Zhuoling Chi; Junying Lü; Yaping Guo (Journal of Environmental Chemical Engineering, 2026)

Seismic rock-physics inversion for petrophysical parameters in deep coalbed methane reservoirs with complex pore structures - Qiang Guo; Yang Chen; Yaping Huang; Jing Ba (Journal of Applied Geophysics, 2026)

Enhancing the leaching of copper oxide ores with high contents of calcium-magnesium alkaline bearing gangue by carboxymethyl chitosan - Jinrui Zhou; Wei Guo; Siqi Yang; Xianping Luo; Louyan Shen; Zhiyong Gao; Hongbo Zhao; Yaping Liu (Minerals Engineering, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Soil microbial niche differentiation in response to nutrient limitation during post-agricultural succession - Haibin Kang; Yue Xue; Lucie A. Malard; Mingming Xing; Yaping Guo; Dexiang Wang (CATENA, 2026)

Dynamics of positive leader branching in long air gaps: A statistical exploration - Lili Guo; Xiangen Zhao; Xiankang Wang; Xiaopeng Liu; Yao Yao; Yaping Du; Junjia He (Atmospheric Research, 2026)

Deformation and Reconstruction of Coastal Typhoon Wind Fields in Hangzhou Bay - Li Li; Jiayi Guo; Zhiguo He; Tao Feng; Yuezhang Xia; Honghua Zou; Yaping Zha; Rong Zhou; Ye Zhu; Wenjun Zhu (Journal of Marine Science and Engineering, 2026)
Coastal typhoon deformation plays a critical role in determining typhoon tracks, intensity changes, precipitation and related flooding, storm surges, and typhoon waves, and thus is highly associated with coastal disaster patterns. This study proposes a three-level framework for typhoon wind field modeling through the integration of geometric characterization with physical-informed reconstruction. At its core, an elliptical fitting method is developed based on second-order moments to quantify the structural asymmetries. This geometric fitting method is incorporated into the reconstruction method of Holland–Miyazaki, creating a physically consistent model capable of simulating typhoon deformation processes during landfall. Validation through high-resolution Weather Research and Forecasting (WRF) simulations of Typhoon Chan-hom (2015) demonstrates the framework’s effectiveness, capturing elliptical eyewall deformation with aspect ratios exceeding 1.5, primarily driven by coastal topography and surface friction interactions. The method is further validated through Typhoon Mitag (2019), with mean wind component errors below 1 m/s, the average correlation coefficients surpassing 0.9, and wind direction mean absolute errors largely below 10°. This research provides a practical framework for quantifying and characterizing the wind field deformation during typhoon landfall in coastal regions, thereby supporting ther operational forecasting and disaster reduction in vulnerable coastal regions.

Promoting the lattice oxygen mechanism via electronic modulation: Cobalt doping and heterointerface effects in RuO2@CuO for enhanced acidic oxygen evolution catalysis - Yuhe Zhang; Yuhui Sun; Yuchen Yang; Yaping Tang; Wei Jiang; Xianyu Chu; Chunbo Liu; jihui Lang; Yuanyuan Wu; Feifan Guo (Chemical Engineering Journal, 2026)

Ectomycorrhizal and saprotrophic fungi are linked to reduced pathogenic fungi across roots and rhizosphere soils of major afforestation species in northeastern China - Wen Guo; Xiangxia Yang; Yaping Liu; Xiaoding Lin; Le Chang; Yaru Wei; Mingming Xia; Minghao Lv; Kazuo Isobe (Soil Ecology Letters, 2026)

Design, synthesis, and biological evaluation of glycyrrhetinic acid–cinnamamide derivatives as HMGB1/TLR4 pathway inhibitors for sepsis-induced liver injury - Jiao Wang; Tian Guo; Zhe Zheng; Yaping Zhang; Zhian Zha; Xiaohan Zhang; Jie Song; Dongyi Wei; Jianbin Yang (Molecular Diversity, 2026)

Occurrence of mycotoxins contamination in commercial feline and canine foods from China - Yaping Guo; Wei An; Xiumin Wang; Bing Han; Hui Tao; Bianfang Liu; Zhenlong Wang; Jinquan Wang (Mycotoxin Research, 2026)

Profiling 32 alkaloid compounds from Macleaya cordata by UPLC-DAD–QTOF-MS/ms - Xinji Zhou; Yuqing Peng; Hao Zhou; Wenyan Wang; Gui Yi; Qi Xia; Yaping Guo; Lianwu Xie (Natural Product Research, 2026)

Construction of platinum/cobalt aluminate heterostructured catalyst via spent catalyst recycling for photo-Fenton-like degradation of malathion - Qiancheng Zhou; Jupei Zhang; Qiuhao Shu; Fengshan Yu; Yaping Guo (Journal of Water Process Engineering, 2026)

Orchestrating ion conduction and interface stability with a montmorillonite filler for dendrite-free and shuttle-free quasi-solid zinc-iodine batteries - Yaping Wang; Xingyun Yang; Miaomiao Zhao; Wenyan Wang; Bin Guo; Yifang Zhang (Chemical Engineering Journal, 2026)

Interface layer-assisted construction of metal organic framework based porous liquids for high performance CO2 selective separation - Zheng Dong; Yangyang Xin; Bowen Xiang; Ruilu Yang; Menglin Zhu; Baolu Cui; Chenjiao Xie; Shuangshuang Long; Wenwu Zhou; Jianwei Liu; Libing Qian; Hongze Guo; et al. (Journal of Environmental Chemical Engineering, 2025)

Electro-enhanced adsorption and ionization-promoted hydrolysis for 3-cyanopyridine in high-salinity wastewater: Process optimization and mechanistic insights - Yaping Guo; Xinhua Huang; Hongying Chen; Mengyao Ren; Xiang Liu; Xiaoxiao Zhai; Kanming Wang (Journal of Water Process Engineering, 2025)

Physical aeration mechanism of SDBS wastewater in a tank aerated by a microporous tube system - Yaping Guo; Mengyao Ren; Chenglang Huang; Xinhua Huang; Xiang Liu; Xiaoxiao Zhai; Qingrong Shu (Chemical Engineering Journal, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

Neonatal Fc receptor participates in endocytosis of Fc fusion protein in vivo and in vitro - Yaping Zhou; Yanfang Wang; Hongmei Zhao; Ting Guo; Yongqing Hao (Veterinary Immunology and Immunopathology, 2025)

Role of HSP40 proteins in genome maintenance, insulin signaling and cancer therapy - Yaping Huang; Guo-Min Li (DNA Repair, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

Biodetoxification of both AFB1 and ZEN by Bacillus subtilis ZJ-2019–1 in gastrointestinal environment and in mice - Jianwen Wu; Wei An; Zhenlong Wang; Boquan Gao; Jiaxue Wang; Ya Zhao; Bing Han; Hui Tao; Yaping Guo; Jinquan Wang; Xiumin Wang (Mycotoxin Research, 2025)

Enhancing cardiac regeneration: direct reprogramming of fibroblasts into myocardial-like cells using extracellular vesicles secreted by cardiomyocytes - Yao Yao; Yuexin Yu; Yaping Xu; Yingtian Liu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

Natural products from Camellia oleifera fruit and its comprehensive utilisation - Yuqing Peng; Hao Zhou; Anlin Zhang; Yaping Guo; Lianwu Xie; Deyi Yuan (Natural Product Research, 2025)

Ghβ-LCY1 influences metabolism and photosynthetic in Gossypium hirsutum - Yanmin Qian; Yaping Wang; Yu Zhang; Zongyan Chu; Mengxin Shen; Cheng Zhang; Lihua Huang; Zhihua Yang; Kaiwen Ren; Yuanyuan Shi; Tingting Jiao; Baoting Yang; et al. (Plant Science, 2025)

Fermentation of soymilk by strains with high conversion ability to soy isoflavones: Strain screening, flavor characteristics, antioxidant properties, and in vitro digestion - Yaping Zheng; Kaiqi Gao; Zimu Li; Yinzhi Zhang; Xuejian Li; Wei Zhang; Ling Guo; Yu Zhang; Yujun Jiang (Food Bioscience, 2025)

Hydrogels in cardiac tissue engineering: application and challenges - Yaping Xu; Yuexin Yu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

A lightweight prediction model for global ionospheric total electron content based on attention-BiLSTM - Chao Han; Yaping Guo; Ming Ou; Dandan Wang; Chenglong Song; Ruimin Jin; Weimin Zhen; Peirui Bai; Xiaorui Chong; Xiaoni Wang (Advances in Space Research, 2025)

Efficiently catalytic purification of indoor formaldehyde upon Co-N sites derived from ZIF-67 carbonization - Zhaoying Di; Runduo Zhang; Xiaonan Guo; Hanxiao Shen; Sebastien Royer; Jingbo Jia; Ying Wei; Yaping Li; Lirong Zheng (Fuel, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Conceptual design of an improved ammonia refining process for coal chemical wastewater - Jingtao Guo; Chao Pan; Yaping Liu; Xingming Jin; Bingxiao Feng; Hengjun Gai (Journal of Water Process Engineering, 2024)

Selective recovery of platinum from spent catalysts to fabricate platinum/amorphous manganese oxide/corrugated silica carrier for formaldehyde removal - Fengshan Yu; Maolin Tian; Xueli Wang; Wenjie Zhang; Chunxia Wang; Jiawei Wen; Junlian Wang; Yaping Guo; Guoyong Huang (Journal of Environmental Chemical Engineering, 2024)

Unraveling immobilization mechanisms of Cd in soil by MgO-modified palygorskite/biochar composite: DFT calculation and combined-artificial aging - Kunpeng Yang; Bingyue Guo; Kai Shen; Wenxuan Luo; Bin Zhang; Yuxuan Hua; Yaping Zhang (Journal of Environmental Management, 2024)

Rill erosion and controlling factors on highway side-slopes in the permafrost region - Rui Li; Lilei Wu; Longxi Cao; Yaping Kong; Guo Chen; Ting Wu (Journal of Mountain Science, 2024)

Amino/MnO2 combined modified biochar for enhancing Pb2+ and Cd2+ removal and mechanisms from aqueous solution - Kunpeng Yang; Kai Shen; Bin Zhang; Yuxuan Hua; Bingyue Guo; Yaping Zhang (Journal of Environmental Chemical Engineering, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Bacterial community network complexity and role of stochasticity decrease during primary succession - Yucheng He; Binu M. Tripathi; Jie Fang; Zihao Liu; Yaping Guo; Yue Xue; Jonathan M. Adams (Soil Ecology Letters, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

A water quality prediction approach for the Downstream and Delta of Dongjiang River Basin under the joint effects of water intakes, pollution sources, and climate change - Yaping Huang; Yanpeng Cai; Yanhu He; Chao Dai; Hang Wan; Hongjiang Guo (Journal of Hydrology, 2024)

Recalcitrant components accumulation in dissolved organic matter decreases microbial metabolic quotient of red soil under long-term manuring - Xiao Yang; Shuai Zhang; Dong Wu; Yaping Huang; Lu Zhang; Kailou Liu; Huiqiao Wu; Shengli Guo; Wenju Zhang (Science of The Total Environment, 2024)

An integrated simulation-optimization approach for combined allocation of water quantity and quality under multiple uncertainties - Yaping Huang; Yanpeng Cai; Chao Dai; Yanhu He; Hang Wan; Hongjiang Guo; Pingping Zhang (Journal of Environmental Management, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Interactive effects of urine components and treatment conditions on antibiotic degradation of combined system integrating thermally activated peroxydisulfate and membrane distillation using machine learning - Yaping Lyu; Zifu Li; Zhiling Guo; Iseult Lynch; Peng Zhang; Shikun Cheng (Chemical Engineering Journal, 2024)

Methanogen–methanotroph community has a more consistent and integrated structure in rice rhizosphere than in bulk soil and rhizoplane - Wenqi Wang; Yaping Guo; Lin Yang; Jonathan Miles Adams (Molecular Ecology, 2024)
Methanogenic and methanotrophic microbes together determine the net methane flux from rice fields. Despite much research on them as separate communities, there has been little study of combined community patterns, and how these vary between the rhizoplane (root surface), rhizosphere (soil surrounding the root) and bulk soil around rice plants, especially at larger spatial scale. We collected samples from 32 geographically scattered rice fields in east central China, amplicon targeting the mcrA gene for methanogenesis and pmoA gene for methanotrophy by using high‐throughput sequencing. Distinct communities of both methanogens and methanotrophs occurred in each of the three compartments, and predominantly positive links were found between methanogens and methanotrophs in all compartments indicating cross‐feeding or consortia relationships. Methanogens were acting as the network hub in the bulk soil, and methanotrophs in rhizoplane. Network complexity and stability was greater in the rhizosphere than rhizoplane and bulk soil, with no network hubs detected, suggesting the strongest effect of homeostatic influence by plant occurred in the rhizosphere. The proportion of determinism (homogeneous selection) and distance–decay relation (DDR) in rhizoplane was consistently lower than that in the rhizosphere for both communities, indicating weaker phylogenetic clustering in rice root surface. Our results have provided a better understanding of CH 4 oxidation and emission in rice paddy fields and future agriculture management could take into consideration of the subtle variation among different soil compartments and interactions within methanogenic and methanotrophic communities.

Research on the spatiotemporal evolution and influencing factors of urbanization and carbon emission efficiency coupling coordination: From the perspective of global countries - Dalai Ma; Yin Yan; Yaping Xiao; Fengtai Zhang; Haoran Zha; Ruonan Chang; Jiawei Zhang; Zuman Guo; Bitan An (Journal of Environmental Management, 2024)

Biological functions of active ingredients in quinoa bran: Advance and prospective - Feiyan Yang; Tianyi Guo; Yaping Zhou; Shuai Han; Shuguo Sun; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Radiation source terms analysis and classification of radioactive waste for the decommissioning of the first HWRR reactor in China - Yaping Guo; Peng Nie; Ruizhi Li; Lijun Zhang; Zelong Zhao (Environmental Science and Pollution Research, 2024)

Efficient separation of cresol isomers using azeotropic coupling pressure-swing distillation: From separation mechanism to process integration - Chao Pan; Jingtao Guo; Yaping Liu; Bingxiao Feng; Guoxuan Li; Hengjun Gai; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2024)

Dynamic multi-objective path-order planning research in nuclear power plant decommissioning based on NSGA-II - Zehuan Zhang; Yaping Guo; Qian Tao (Annals of Nuclear Energy, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Unraveling the stereoscopic gene transcriptional landscape of zebrafish using FishSED, a fish spatial expression database with multispecies scalability - Cheng Guo; Weidong Ye; Danying Cao; Mijuan Shi; Wanting Zhang; Yingyin Cheng; Yaping Wang; Xiao-Qin Xia (Science China Life Sciences, 2024)

Baicalin − 2- ethoxyethyl ester alleviates renal fibrosis by inhibiting PI3K/AKT/NF-κB signaling pathway - Jiacun Li; Ke Zhang; Mei Xu; Huanyue Cui; Yaping Guo; Dahong Yao; Wenhua Chen; Huaimin Liang; Hangyu Wang; Jinhui Wang (Toxicology and Applied Pharmacology, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Distinct biogeographic patterns in Glomeromycotinian and Mucoromycotinian arbuscular mycorrhizal fungi across China: A meta-analysis - Zihao Liu; Jie Fang; Yucheng He; Gary D. Bending; Bin Song; Yaping Guo; Xiaojie Wang; Zemin Fang; Jonathan M. Adams (Science of The Total Environment, 2024)

An approach to complex transboundary water management in Central Asia: Evolutionary cooperation in transboundary basins under the water-energy-food-ecosystem nexus - Lidan Guo; Yueting Wu; Feng Huang; Peiran Jing; Yaping Huang (Journal of Environmental Management, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Fisetin, a dietary flavonoid, promotes transintestinal cholesterol excretion through the activation of PPARδ - Yao Guo; Bing Liu; Yaping Geng; Ke Chen; Junyan Li; Xiangju Yin; Shenshen Zhang (Food Research International, 2024)

pH is the major predictor of soil microbial network complexity in Chinese forests along a latitudinal gradient - Dorsaf Kerfahi; Yaping Guo; Ke Dong; Qingkui Wang; Jonathan M. Adams (CATENA, 2024)

Osthole protects H9c2 cardiomyocytes against trastuzumab-induced damage by enhancing autophagy through the p38MAPK/mTOR signaling pathway - Huan Hou; Yaping Yang; Rong Chen; Zhiping Guo (Toxicology in Vitro, 2023)

Cytotoxic 4-phenylcoumarins from the flowering buds of Mesua ferrea - Xiya Chen; Zhiying Liu; Bi Zhong; Mengjie Zhu; Han Yao; Xiaojie Chen; Yongchao Lu; Shuyun Wang; Yaping Guo (Natural Product Research, 2023)

Spatiotemporal evolution and influencing factors of water resource green efficiency in the cities of the Yangtze River Economic Belt - Dalai Ma; Bitan An; Jiawei Zhang; Fengtai Zhang; Yaping Xiao; Zuman Guo (Environmental Science and Pollution Research, 2023)

Simple and efficient strategy for α-MnO2/C by in-situ synthesis and its performance for degrading urea process wastewater - Yanli He; Shuguang Shen; Ying Wang; Chenyuan Guo; Yaping Yuan; Yaru Fan; Lili Zhang; Yuyan Song (Journal of Environmental Chemical Engineering, 2023)

Establishment of a halotolerant bioremediation platform from Halomonas cupida using synthetic biology approaches - Wanwan Zhao; Weini Xiong; Yujie Liu; Hongfu Guo; Siqi Wang; Yaping Chen; Ruihua Liu; Bingzhi Li; Chao Yang (Chemical Engineering Journal, 2023)

Inhibition of soluble calcium ions in municipal solid waste incineration fly ash by carbonate in an electrokinetic environment - Qingxiang Wang; Shilin Wang; Yifan Zhang; Junqi Liu; Yaping Guo; Tao Huang; Yaojie Tu; Xin He; Ding Wang (Fuel, 2023)

What were the spatiotemporal evolution characteristics and the influencing factors of urban land green use efficiency? A case study of the Yangtze River Economic Belt - Dalai Ma; Jiawei Zhang; Fengtai Zhang; Yaping Xiao; Hongmei Tan; Zuman Guo; Bitan An (Environmental Monitoring and Assessment, 2023)

Spatiotemporal differentiation of carbon emission efficiency and influencing factors: From the perspective of 136 countries - Yaping Xiao; Dalai Ma; Fengtai Zhang; Na Zhao; Ling Wang; Zuman Guo; Jiawei Zhang; Bitan An; Yuedong Xiao (Science of The Total Environment, 2023)

A TiO2/Si carrier derived from photovoltaic solid waste to assemble Ag3PO4/Co3(PO4)2/TiO2/Si heterostructure for enhancing visible-light photocatalytic activity - Qing Huang; Wenyi Yuan; Qinfei Ke; Yaping Guo; Lincai Wang; Chenfeng Wang (Journal of Environmental Chemical Engineering, 2023)

Corrigendum to ‘Polyvinyl alcohol/starch-based film incorporated with grape skin anthocyanins and metal-organic framework crystals for colorimetric monitoring of pork freshness ‘[Food Chem. 395 (2022) 133613] - Xueqi Lin; Ning Li; Qiao Xiao; Yaping Guo; Jie Wei; Tianhui Jiao; Qingmin Chen; Quansheng Chen; Xiaomei Chen (Food Chemistry, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

Interferon-τ -induced ISG15-AS regulates endometrial receptivity during early goat pregnancy - Ruixue Zhang; Xinyan Guo; Hanbing Li; Zuhui Li; Suhua Gong; Haijing Li; Yongjie Ma; Haokun Liu; Chuxi Gao; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2023)

Improved thermal tolerance of ovotransferrin against pasteurization by phosphorylation - Yaping Liu; Jiajie Wang; Chenxin Huang; Bingying Cai; Fuxuan Guo; Lin Chen; Xianchao Feng; Meihu Ma (Food Chemistry, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Metabolite profiling in albino tea mutant Camellia sinensis ‘Fuyun 6’ using LC–ESI–MS/MS - Xinying Lin; Xuejin Chen; Pengjie Wang; Yucheng Zheng; Yongchun Guo; Yaping Hong; Ruxing Yang; Naixing Ye (Trees, 2022)

A 90-Day Subchronic Toxicity Study of Consumption of GH-Transgenic Triploid Carp in Wistar Rats - Jingya Guo; Yongming Li; Yaping Wang; Boyong Chen; Yingxin Hu; Yasheng Musha; Xiaoyun He; Tao Tong; Kunlun Huang (Fishes, 2022)
Genetic modification (GM) offers an alternative strategy to conventional animal breeding. The present study was carried out to investigate the potential health effects of the consumption of growth hormone-transgenic triploid carp (GH-ttc) through a 90-day subchronic rodent feeding study. Wistar rats (n = 10/sex/group) were given formulated diets containing GH-ttc or non-GM carp at an incorporated rate of 2.5%, 5%, or 10% (w/w) for 90 days. An additional control group of rats (n = 10/sex/group) was fed a basic rodent diet. During the 90-day study, clinical observation, ophthalmic examination, body weight, and food intake were evaluated. At the end of the study, rats were killed, and the hematology, serum chemistry, urine test, necropsy, and histopathology were assessed. Compared with the non-GM carp and the basic control groups, no biologically significant differences were observed on clinical signs of toxicity, body weights, food intake, hematology, serum chemistry, urinalysis, organ weight, and histopathology on selected organs for the GH-ttc group. The results of this 90-day subchronic feeding study indicated that, at the dose level used in this study, consumption of GH-ttc showed no subchronic toxicity to Wistar rats.

Preparation and performance evaluation of novel magnetic porous carriers in fluidized bed bioreactor for wastewater treatment - Qibang Tong; Guixin Wang; Maolian Chen; Yaping Chen; Yong Guo (Biodegradation, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Pituitary Adenylate Cyclase-Activating Polypeptide Protects Against Cognitive Impairment Caused by Chronic Cerebral Hypoperfusion - Xiaosu Guo; Ye Tian; Yaping Yang; Shiping Li; Li Guo; Jiong Shi (Molecular Neurobiology, 2021)

Anaerobic semi-fixed bed biofilm reactor (An-SFB-BR) for treatment of high concentration p-nitrophenol wastewater under shock loading conditions - Maolian Chen; Ningning Yu; Yaping Chen; Qibang Tong; Yong Guo (Biodegradation, 2021)

Cotton seedling drought tolerance is improved via salt preconditioning - Rong Fan; Xiujuan Su; Yaping Guo; Fenglei Sun; Yanying Qu; Quanjia Chen (Protoplasma, 2021)

Two novel compounds from green walnut husks ( Juglans mandshurica Maxim.) - Hong Yang; Chunli Gan; Yaping Guo; Liyuan Qu; Shuang Ma; Yanbin Ren; Xingwen Wang; Libo Wang; Jian Huang; Jinhui Wang (Natural Product Research, 2020)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

Quantitative proteomics analysis reveals the tolerance of Mirabilis jalapa L. to petroleum contamination - Shuisen Chen; Hui Ma; Zhifu Guo; Yaping Feng; Jingwei Lin; Menghua Zhang; Ming Zhong (Environmental Science and Pollution Research, 2017)

ace-3 plays an important role in phoxim resistance in Caenorhabditis elegans - Yan Han; Shaojuan Song; Yaping Guo; Jianzhen Zhang; Enbo Ma (Ecotoxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Spatial and temporal variations of global frictional torque during the period 1948–2011 - He Gong; Mei Huang; Lin Zhu; Shengli Guo; Yaping Shao (Journal of Meteorological Research, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Trends of subtype variation of human immunodeficiency virus type 1 in Zhejiang Province, China - Yaping Yao; Ruolei Xin; Jiezhe Yang; Yun Xu; Jiafeng Zhang; Yan Xia; Xiaohong Pan; Zhihong Guo; Yanhui Song (Virus Genes, 2015)

Changes to Cuticle Surface Ultrastructure and Some Biological Functions in the Nematode Caenorhabditis Elegans Exposed to Excessive Copper - Shaojuan Song; Yaping Guo; Xiaomin Zhang; Xueyao Zhang; Jianzhen Zhang; Enbo Ma (Archives of Environmental Contamination and Toxicology, 2014)

Hepatocyte Nuclear Factor 4 Alpha and Farnesoid X Receptor Co-regulates Gene Transcription in Mouse Livers on a Genome-Wide Scale - Ann M. Thomas; Steve N. Hart; Guodong Li; Hong Lu; Yaping Fang; Jianwen Fang; Xiao-bo Zhong; Grace L. Guo (Pharmaceutical Research, 2013)

Epimerization of epigallocatechin gallate to gallocatechin gallate and its anti-diabetic activity - Lianwu Xie; Yaping Guo; Bo Cai; Jing Yang (Medicinal Chemistry Research, 2013)

Effect of chlorogenic acid on LPS-induced proinflammatory signaling in hepatic stellate cells - Haitao Shi; Lei Dong; Xiaoyan Dang; Yaping Liu; Jiong Jiang; Yan Wang; Xiaolan Lu; Xiaoyan Guo (Inflammation Research, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Antigenic analysis of grass carp reovirus using single-chain variable fragment antibody against IgM from Ctenopharyngodon idella - CongLin Chen; XiaoYun Sun; LanJie Liao; ShaoXiang Luo; ZhouQuan Li; XiaoHua Zhang; YaPing Wang; QionLin Guo; Qin Fang; HePing Dai (Science China Life Sciences, 2013)

The complete mitochondrial genome of the butterfly Apatura metis (Lepidoptera: Nymphalidae) - Min Zhang; Xinping Nie; Tianwen Cao; Juping Wang; Tao Li; Xiaonan Zhang; Yaping Guo; Enbo Ma; Yang Zhong (Molecular Biology Reports, 2012)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

Overexpression of NYGGF4 (PID1) induces mitochondrial impairment in 3T3-L1 adipocytes - Yaping Zhao; Chunmei Zhang; Xiaohui Chen; Chunlin Gao; Chenbo Ji; Fukun Chen; Chun Zhu; Jingai Zhu; Jialin Wang; Lingmei Qian; Xirong Guo (Molecular and Cellular Biochemistry, 2010)

Genetic Variation and Population Structure of Oriental Migratory Locust, Locusta migratoria manilensis, in China by Allozyme, SSRP-PCR, and AFLP Markers - Xianyun Zheng; Yang Zhong; Yihao Duan; Chunxuan Li; Li Dang; Yaping Guo; Enbo Ma (Biochemical Genetics, 2006)